2000
DOI: 10.2175/193864700784545946
|View full text |Cite
|
Sign up to set email alerts
|

Werf: Application of Membrane Bioreactor (Mbr) Technology for Wastewater Treatment

Abstract: One of the most promising and innovative technologies in water reclamation today is the membrane bioreactor (MBR) process. (Adham et al., 1998) However, the limits of the MBR process for wastewater treatment are not very well understood to date. With funding provided by WERF and in-kind contributions provided by the City of San Diego, the project team investigated the MBR process for wastewater treatment. Two MBR pilot units were operated in parallel to effectively evaluate each test condition on domestic was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Cicek et al (2001), working with an EMBR treating synthetic wastewater, found that the specific flux decreased when the F/M reached 1.05 gCOD/gVSS . d. Trussell et al (2000) found that the membrane fouling rate in an SMBR treating municipal wastewater increased at an F/M of 1.10 gBOD/gVSS . d. Because Trussell et al (2000) and Cicek et al (2001) did not operate at constant MLSS, it is possible that the low MLSS values they obtained at high F/Ms were responsible in part for membrane fouling .…”
Section: F/mmentioning
confidence: 98%
See 4 more Smart Citations
“…Cicek et al (2001), working with an EMBR treating synthetic wastewater, found that the specific flux decreased when the F/M reached 1.05 gCOD/gVSS . d. Trussell et al (2000) found that the membrane fouling rate in an SMBR treating municipal wastewater increased at an F/M of 1.10 gBOD/gVSS . d. Because Trussell et al (2000) and Cicek et al (2001) did not operate at constant MLSS, it is possible that the low MLSS values they obtained at high F/Ms were responsible in part for membrane fouling .…”
Section: F/mmentioning
confidence: 98%
“…In previous SMBR experiments on municipal wastewater Trussell et al (2000) obtained a median effluent COD value of 22 mg/L and a 90 th percentile value of 28 mg/L over the range of MCRT values from 1.5 d to 35 d. At an MCRT below 2 d, Trussell et al (2000) found that the effluent COD increased to a median value of 30 mg/L and a 90 th percentile value of 32 mg/L. At an MCRT of 2 d, Cicek et al (2001) found that the median effluent COD increased to 23 mg/L from 3.5 mg/L at a 5-d MCRT.…”
Section: Process Performancementioning
confidence: 99%
See 3 more Smart Citations